243 Mental health status and sexual habits in young patient after acute coronary syndrome. (8th December 2021) - Nicolò, Claudio; Franzino, Marco; Pistelli, Lorenzo; De Sanctis, Giulia; Parisi, Francesca; Migliorato, Alessandro; Grimaldi, Patrizia; Crea, Pasquale; Luzza, Francesco; Carerj, Scipione; Di Bella, Gianluca; Costa, Francesco; et al.
Abstract: Aims: Acute coronary syndrome (ACS) has a huge potential impact on patients' life, and little is known on the long-term effect on mental health in young patients. Methods and results: We included consecutive young patients (≤45 years at presentation) with ACS referred from October 2013 until March 2021 to our clinic. Physical and mental status was evaluated through the standardized SF12 scale for physical (PCS) and mental status (MCS). Depression and perceived stress were evaluated with the patient health questionnaire 9 (PHQ9) and perceived stress scale (PSS). A total of 91 patients have been included and followed for a median of 40 months. History of anxiety or depression at baseline was reported in 1.1% and 2.2%, respectively. Physical and mental health status was impaired in 65.8% and 42.1% of patients, respectively (Figure). Predictors of poorer physical health were lower LVEF, WMSI, and multivessel disease. Predictors of poorer mental health were age and nuisance bleeding during follow-up. Mild/moderate depression was reported in 47.3%. Moderate/high stress was reported in 78.1%. 37.1% patients affirmed that their career trajectory worsened after the event and 37.8% declared a reduction of income. 53.8% declared mild to significant changes in their sexual activity, while 83.8% declared to have received no advises on sexual activity from their Doctor. Conclusions: In conclusion, ACS is a dramatic event with a significant impact on young patients' life at a physical, mental, and social level. Measures of social/psychological support in the aftermath of the event merit consideration in future research.